PENGENDALIAN ALIH FUNGSI LAHAN SAWAH YANG BERKELANJUTAN DI KECAMATAN TAMBANG, KABUPATEN KAMPAR, RIAU - Chendy Prima Sari; Zulfan Saam; Ridwan Manda Putra (Program Pascasarjana Universitas Riau, 2021)
The phenomenon of paddy fields conversion in Kampar Regency which continues to increase from year to year had caused decreasing paddy fields area and threatening food supply capacity. The purpose of this study was to analyze the index and the status of the sustainability of control over the paddy fields conversion and to find out the sensitive attributes of the sustainability of control over the paddy fields conversion in Tambang Sub-District, Kampar Regency. This research was conducted in Aur Sati Village, Balam Jaya Village and Pulau Permai Village, Tambang Sub-District, Kampar Regency from October 2020 to January 2021. The method used was the survey method with a quantitative approach. The sampel of farmers in this study were 88 people who were selected by purposive sampling. Data collection was done by observation, interviews, and literature study. This study used questionnaires as an instrument to collect data. The analytical method used in this research was the sustainability analysis carried out with the Multi-Dimensional Scaling (MDS) analysis approach with the Rap-Paddy Field tool which has been modified from Rapfish program. The results showed that the control of the paddy fields conversion in Aur Sati Village has been going very well, this can be seen from the sustainability index value of each dimension in the range of 52.4 - 83.9% (fairly - highly sustainable). On the other hand, the sustainability index value of each dimension in Balam Jaya Village ranges from 35.9 - 48.2% (less sustainable), this showed that paddy fields conversion in this village has not been well controlled. While in Pulau Permai Village, the economic dimension had a sustainability index value of 48.2% (less sustainable) and there were 2 (two) dimensions that were classified as fairly sustainable, namely the ecological dimension of 64.4% and the social dimension of 52.3%. These data provided information that the control of paddy fields conversion in Pulau Permai Village is still ecologically and socially oriented, and ignores the economic dimension. There were sensitive attributes that need to be given top priority in planning the sustainability of control over the paddy fields conversion in Tambang Sub-District, Kampar Regency, namely price stability, product markets, traditional leaders, cultivation techniques and availability of RTRW.